2016
DOI: 10.1159/000453278
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcome in Subthalamic Nucleus Stimulation Surgeries with Electrodes Passing through the Caudate Nucleus

Abstract: Background: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) in Parkinson disease (PD) is associated with postoperative cognitive decline. One of the proposed underlying mechanisms is the surgical procedure with the lead trajectory penetrating the caudate nucleus. Objective: To study whether penetration of the caudate nucleus affects neuropsychological outcome. Methods: Neuropsychological and imaging data of 30 PD patients who underwent bilateral STN DBS were analysed. Lead trajectories were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
3
18
1
1
Order By: Relevance
“…They concluded that there was no influence on cognitive outcomes due to CN penetration. Isler et al [11] evaluated 30 cases (all bilateral) of STN DBS for PD with usage of postoperative MRI and CT and noted 10 patients with CN penetration. They found a significant difference in the Trail Making Test Part B after 3 months of follow-up; however, they found no influence on cognitive outcomes due to CN penetration after 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They concluded that there was no influence on cognitive outcomes due to CN penetration. Isler et al [11] evaluated 30 cases (all bilateral) of STN DBS for PD with usage of postoperative MRI and CT and noted 10 patients with CN penetration. They found a significant difference in the Trail Making Test Part B after 3 months of follow-up; however, they found no influence on cognitive outcomes due to CN penetration after 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of the data was applied, which facilitated comparisons between subjects; however, the individual interrelationship between DBS trajectory and CN was lost [9, 17]. Taking the findings of Isler et al [11] into account, these differences are possibly due to short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations